Under the never sky - Rossi, Veronica (Rossi, Veronica. Under the never sky trilogy, 2012)
Aria has lived her whole life in the protected dome of Reverie. Her entire world confined to its spaces, she's never thought to dream of what lies beyond its doors. So when her mother goes missing, Aria knows her chances of surviving in the outer wasteland long enough to find her are slim. Then Aria meets an outsider named Perry. He's searching for someone too. He's also wild -- a savage -- but he might be her best hope at staying alive. If they can survive, they are each other's best hope for finding answers.